Bedaquiline resistance in Mycobacterium tuberculosis during antimycobacterial therapy and its impact on clinical outcomes (clinical cases) - O. M. Raznatovska; R. M. Yasinskyi; O. S. Shalmin; A. V. Fedorets; O. A. Svitlytska (Zaporožskij Medicinskij Žurnal)
Aim. To analyze the nature of Bedaquiline (Bdq) resistance in Mycobacterium tuberculosis (MBT) during antimycobacterial therapy (AMBT) in patients with multidrug-resistant tuberculosis (MDR-TB), its impact on clinical outcomes and to detect risk factors for the Bdq drug resistance development on the example of own observed clinical cases.